Sentiscope: A System for Sentiment Analysis in Daily Horoscopes - Merkler, Danijela; Agić, Željko (2013)
We present Sentiscope – a prototype system for collecting, sentiment annotation and visualization of daily horoscopes from news portals written in Croatian. System architecture and evaluation is provided and the system itself is made available to users on the web. The sentiment analysis component is based on rules implemented as finite state transducer cascades in NooJ development environment.
Projekt MZOS
ENG